The mature larva of Poemenia albipes Cresson (Hymenoptera: Ichneumonidae, Poemeniinae) and a review of the biology of Nearctic Poemenia - Wahl, David B. (Zootaxa, 2020)
The mature larva of Poemenia albipes is figured and described, providing the first knowledge of the larval morphology of this genus. Poemenia is considered to be an ectoparasitoid on the basis of this information. The implications for the larval morphology of the Poemeniinae are discussed. The biology of Nearctic Poemenia is reviewed, with the conclusion that the genus is parasitic upon small xylophilous Apoidea that either make their tunnels or utilize those made by other insects.